PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA PESERTA DIDIK - Rezka Agussantri; Zulkarnain Zulkarnain; Armis Armis (Faculty of Educational sciences, UIN Syarif Hidayatullah Jakarta, 2020)
This research aims to improve the learning process and increase mathematics learning outcomes by implementing the Problem Based Learning model of the students in class VIII.6 MTs Negeri 1 Pekanbaru. Subject of this research are students of class VIII.6 MTs Negeri 1 Pekanbaru in odd semester of academic year 2019/2020 which consist of 31 students. This form of research is a classroom action with two cycles. Data collection using observation sheets and learning outcome test. The result of the research showed that the learning process has improved from cycle 1 to cycle 2, seen from the achievements of mathematics learning outcomes of students in aspects oof knowledge and skills. The data obtained from the student’s achievement test shows that the percentage of students who reached the Minimum Mastery Criteria (MMC) aspek of knowledge has increased is 16,12% and 29,03% on aspek of skill. The conclusion of this research is implementation of the Problem Based Learning model can improve mathematics learning outcomes of students.